Proses elektroplating nikel dengan variasi jarak anoda katoda dan tegangan listrik pada baja ST-41 - Billy Permadi; Asroni Asroni; Eko Budiyanto (TURBO [Tulisan Riset Berbasis Online], 2019)
Electroplating process is a coating process where the deposition of a thin metal coating occurs on a coated surface using direct current and constant voltage. The process of finishing metal products uses Nickel as a coating that serves to improve the properties of the metal so that it resists corrosion and attach importance to the appearance of the metal surface. The metal coating process is carried out by electroplating technique with Nickel which occurs as an anode, and electrolyte uses in this process contained Nickel Sulphate. This study aims to determine the effect of distance variations and electrical pressure on layer thickness and adhesive strength. Anode Material coated with ST-41 Steel Plate with dimensions of 70 x 25 x 20 mm. While the cathode uses nickel (Ni) with dimensions of 10 x 20 x 20 mm. Cathode distance variations with anodes 5, 10, and 15 cm and electrical voltage variations of 3.5 Volts, 5 Volts, and 7.5 Volts. Bath time of 40 minutes and adhesion testing using the Posi Test AT-M Adhesion Tester. The results obtained from this study are the distance of the cathode with the best anode found at a distance of 5 cm and a voltage of 7.5 volts with a thickness of 0.0160 mm. Then the best voltage is at 7.5 Volts with a sticky strength value of> 21.53 MPa.Keywords: Electroplating, Nickel, Anode, Cathode, ST-41 Steel.